Technology-integration in language studies: Cultivating future paradigms - Noor Raha, Mohd Radzuan (Penerbit UMPSA, 2024)
The language education landscape is rapidly evolving, driven by digital tools and technological innovations that have transformed traditional teaching and learning approaches. This book emerges from the need to explore, understand, and document these dynamic shifts in the English language learning environment. Comprising seven chapters, each chapter examines how different technological platforms can be leveraged to foster collaborative learning, improve student engagement, and address the challenges educators and learners face. Tools like Coggle, Storyboard, Google Docs, Canva, and AI-owered platforms such as ChatGPT can revolutionise learning, but only if their application is carefully understood and tailored to the needs of educators and learners. The chapters collectively offer practical solutions, theoretical insights, and evidence-based recommendations for those committed to advancing language education in a digital age. This book attempts to bridge that gap by exploring the use of these tools in diverse educational contexts. This collection is significant as it is based on the research conducted by Master of Science in Technology-integrated Language Studies (MScTiLS) students as part of their final year projects. These students, guided by their curiosity and dedication, explored the intersection of technology and language learning to enhance the educational experience of English as a Second Language (ESL) learners. Their contributions form the foundation of this book, and their research reflects their individual academic journeys and addresses the broader challenges in today’s educational landscape. This book showcases real-world applications of technology in education rooted in authentic research and innovative thinking by including their work.